Informality and macroeconomic fluctuations - Norbert M. Fiess; Marco Fugazza; William F. Maloney (Institute for the Study of Labor (IZA), 2008)
This paper examines the adjustment of developing country labor markets to macroeconomic shocks. It models as having two sectors: a formal salaried (tradable) sector that may or may not be affected by union or legislation induced wage rigidities, and an informal (nontradable) self-employment sector facing liquidity constraints to entry. This is embedded in a standard small economy macro model that permits the derivation of patterns of comovement among relative salaried/self-employed incomes, salaried/self-employed sector sizes and the real exchange rate with respect to different types of shocks in contexts with and without wage rigidities. The paper then explores time series data from Argentina, Brazil, Colombia and Mexico to test for cointegrating relationships corresponding to the patterns predicted by theory. We confirm episodes of expansion of informal self-employment consistent with the traditional segmentation views. However, we also identify episodes consistent with the sectoral expansion being driven by relative demand or productivity shocks to the nontradables sector that lead to procyclical behavior of the informal self-employed sector.
urn:nbn:de:101:1-20080605148
Keywords: F41; 330; Informality; labor market dynamics; self-employment; real exchange rates; Arbeitsmarkt; Kaufkraftparität; Schock; Wirtschaftliche Anpassung; Dualökonomie; Informeller Sektor; Theorie; Argentinien; Brasilien; Kolumbien; Mexiko